Caribbean at another crossroad: statement - Nicholls, Sir Neville (CDB [Bridgetown]BB, 1992)
Reviews CDB's annual report and performance during 1991. Focuses on some threats to our current well-being such as a decrease in preferential trading arrangements, as well as an increasing decline in concessionary financing for services that have traditionally favoured this region. Looks at an appropriate response, which is to adjust to the threat. Examines the global environment in which we must formulate our policies, and focuss on CDB's role. Concludes that we must become more competitive and dynamic.